Evaluation of anesthesiology residents in the diagnosis and control of malignant hyperthermia: comparison of three scenarios of realistic simulation ‒ a cross-sectional controlled study - Mariana F.L. Neville; Victor Guimarães de Almeida; Pamela Vieira Andrade; Joilson Moura Santos; Masashi Munechika; David Ferez; Mary dos Santos Silva; Leonardo Ayres Canga; Ana Cristina Tripoloni; Thierry Girard; Helga Cristina Almeida da Silva (Brazilian Journal of Anesthesiology, 2025)
Introduction: Simulation-based training is particularly beneficial for rare and life-threatening diseases such as Malignant Hyperthermia (MH). In addition, cognitive aids, including flowcharts and checklists, can be used as guidance in crisis, reducing cognitive demand and simplifying patient care. We assessed the technical and non-technical performance of anesthesiology residents when diagnosing and treating a hypothetical case of MH in three different scenarios. Methods: This was an observational, cross-sectional, and controlled study. Pairs of anesthesiology residents participated in a validated high-fidelity MH realistic simulation in one of three different scenarios: 1) Control (no access to cognitive aids), 2) Poster, or 3) Mobile application. Both poster and mobile application provided a flowchart and information related to MH diagnosis and treatment. Demographic data, perceived stress levels, and technical and non-technical skills were registered and compared among the groups. Results: Thirty residents (5-pairs for each scenario) participated in the simulations. The mean score in the technical skill survey was significantly higher in the poster and mobile application groups compared with the control group (83 [4.4], 83 [3.8], and 74 [8.2], respectively, ANOVA, p = 0.047). A significantly higher score for non-technical skills was also found for the poster and mobile application groups compared with the control group (55 [2.5], 57 [0.8], 52 [2.1], respectively, ANOVA, p = 0.03). Conclusion: In a realistic high-fidelity MH simulation, the participants had satisfactory performance regarding technical and non-technical skills. However, the groups with access to cognitive aids achieved better scores, with no difference between the groups with access to the MH poster and the MH mobile application.